2017
DOI: 10.1111/bjc.12153
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness of voices, self‐compassion, and secure attachment in relation to the experience of hearing voices

Abstract: ObjectivesDeveloping compassion towards oneself has been linked to improvement in many areas of psychological well‐being, including psychosis. Furthermore, developing a non‐judgemental, accepting way of relating to voices is associated with lower levels of distress for people who hear voices. These factors have also been associated with secure attachment. This study explores associations between the constructs of mindfulness of voices, self‐compassion, and distress from hearing voices and how secure attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 53 publications
4
33
0
Order By: Relevance
“…Although this is similar in some respects to “being non‐judgmental,” “letting go” was mentioned specifically in relation to freeing themselves from self‐criticism arising from being labelled as depressed or ill. This seems to be in accordance with studies reporting that improvements in self‐compassion mediate the effects of mindfulness interventions on worry (Keng, Smoski, Robins, Ekblad, & Brantley, ) and self‐compassion is also a core element of mindfulness for voice hearers where participants learn to embrace themselves and their present experiences in order to build hope (Dudley, Eames, Mulligan, & Fisher, ). Letting go may also be an important mechanism of change in improving perceived physical well‐being, a qualitative exploration of yoga for chronic pain reported that participants reframed what it was like to be diagnosed and live with chronic pain, resulting in a reduction of distress despite the sensory aspects of pain being unchanged (Tul et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Although this is similar in some respects to “being non‐judgmental,” “letting go” was mentioned specifically in relation to freeing themselves from self‐criticism arising from being labelled as depressed or ill. This seems to be in accordance with studies reporting that improvements in self‐compassion mediate the effects of mindfulness interventions on worry (Keng, Smoski, Robins, Ekblad, & Brantley, ) and self‐compassion is also a core element of mindfulness for voice hearers where participants learn to embrace themselves and their present experiences in order to build hope (Dudley, Eames, Mulligan, & Fisher, ). Letting go may also be an important mechanism of change in improving perceived physical well‐being, a qualitative exploration of yoga for chronic pain reported that participants reframed what it was like to be diagnosed and live with chronic pain, resulting in a reduction of distress despite the sensory aspects of pain being unchanged (Tul et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…As predicted, high levels of self‐compassion correlated with a low frequency of PLEs and with low levels of PLE‐distress. Thus, our study is in line with previous research, which showed self‐compassion to be associated with less prevalence of psychotic symptoms in people diagnosed with schizophrenia (e.g., Eicher et al ., ) and with less hallucination distress in people who hear voices (Dudley et al ., ). Furthermore as expected, the correlations of self‐compassion with distress were stronger than the correlations with the frequency of PLEs.…”
Section: Discussionmentioning
confidence: 97%
“…Following up on previous studies which found self‐compassion to be associated with less symptoms in a clinical sample (Eicher, Davis, & Lysaker, ) and with lower distress and severity of voices in voice hearers (Dudley, Eames, Mulligan, & Fisher, ), we investigated the association between self‐compassion, PLEs, and PLE‐distress in a community sample. Based on our assumption that a continuous phenotype underlies PLEs, community samples are expected to include a broad spectrum ranging from people experiencing none or few PLEs towards people with more frequent and/or more distressing experiences, indicating proneness towards psychosis (Mark & Toulopoulou, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is formed from the leadership actions when thinking, speaking, and listening to other parties. Previous studies also reveal that this mindfulness practice has a strong connection to the development of compassion to others in one's self (Dudley, Eames, Mulligan, & Fisher, 2018;Van Wietmarschen, Tjaden, Van Vliet, Battjes-Fries, & Jong, 2018). Thought the practice of mindfulness and the ability to 'stop' and bring out clarity from within.…”
Section: He Can Be a Bridge To Like A Keep Information From The Brmentioning
confidence: 96%